Representação da falência do Lehman Brothers durante a crise financeira de 2008 em editoriais americanos e brasileiros: um enfoque crítico da gramática sistêmico-funcional - Alencar, André Luiz Siqueira (2018)
The objective of this dissertation is the critical analysis of the representation made by the media regarding the bankruptcy of Lehman Brothers, one of the largest banking institutions in the world, as well as the actors involved. There are always different ways of saying the same thing, and these modes are not accidental alternatives. Differences in expression bring ideological distinctions, and thus differences of representation. In the decade of 2008, the world went through an economic recession triggered by US mortgage lending, which led to bank failures, unemployment and rising poverty. Lehman Brothers’ bankruptcy is considered one of the most important milestones of the 21st century, equated only with the terrorist attacks of September 11. The analysis will be made in editorials of two newspapers: Folha de S.Paulo and The New York Times, with basic support of the Systemic-Functional Grammar (SFG). The SFG’s theoretical-methodological proposal makes it possible to relate the lexicographic choices of the text microstructure to the macro structure of ideology and force relations, establishing a link between social and individual, macro and micro, social and cognitive typology. This type of approach is especially useful in examining the discourse of different groups with specific ideological characteristics. For SFG, language has the function of constructing three meanings – or metafunctions: ideational (information), interpersonal (interaction) and textual (linguistic organization of metafunctions). SFG also involves Critical Linguistics, to which any aspect of the linguistic structure carries ideological significance – lexical selection, syntactic choice, etc. The research should answer the following questions: (a) How can ideational metafunction, through transitivity, construct the representation concerning Lehman Brothers bankruptcy? (b) What role do interpersonal metafunctions have, through modality and evaluativeness, in this process? The results show that the Brazilian editorial “Cada vez pior” describes and narrates the negative aspects of the crisis, however, without positioning against or in favor of the issue, while the American editorial “Wall Street Casualties” also describes and narrates, but suggests positive aspects of the collapse